Analisis Faktor Penyebab Anak Lamban Belajar (Hambatan Membaca) pada Sekolah Inklusi di SDN Cipete 4 Kota Tangerang - Nurfadhillah, Septy; Aulia, Putri Bunga; Rachmadani, Annisa (Lembaga Yasin AlSys, 2022)
This study aims to analyze the factors that cause slow learning children, especially on reading barriers in the Inclusive School at SDN Cipete 4 Tangerang City. This study uses a qualitative descriptive research approach with data collection methods of observation, interviews, and documentation. The results of the analysis in this study indicate that there are 7 students who are slow learners, especially in reading barriers. The factors that cause slow learners to learn are very broad, more or less the same answer as the factors that cause special needs, but in this slow learner it enters the realm of intelligence barriers where children become slower to process incoming information. The cause can be pre natal (before birth) natal (birth process) post natal (after birth), and environment.